High purity hydrogen production with a 10kWth RESC prototype system. (15th September 2018) - Bock, S.; Zacharias, R.; Hacker, V.
Highlights: Demonstration 10 kWth lab prototype for on-site H2 production. 99.999% pure hydrogen from fixed bed chemical looping. Significant influences of exothermic oxidation on thermal behavior. Characterization of iron-based oxygen carrier for large-scale fixed bed operation. Abstract: The Reformer Steam Iron Cycle (RESC) is suitable to attain high-purity pressurized hydrogen from a broad range of renewables and residues in decentralized on-site applications. This paper introduces a 10 kWth lab prototype system for high purity hydrogen production exceeding 99.999%. The significantly enlarged reactor system comprises of a combined steam reformer and fixed bed chemical looping system within a single unit. A series of experiments was conducted to demonstrate the system applicability for decentralized hydrogen production with an improved process layout. A previously undiscovered hydrogen purity was realized from a fixed-bed chemical looping prototype system. Supplementary, the applied oxygen carrier material was characterized to reveal occurring degradation effects in large-size reactors as a significantly increased thermal stress. A characterization by SEM, EDX, light microscopy and BET methods was performed to exhibit the effects on the pelletised material.